Micro and small enterprises in India - "Das,Keshab. (ed.)" (New Delhi, 2011)
Micro And Small Enterprises In India: The Era of Reforms This book presents a set of analytical and deeply policy-oriented articles on the dynamics of growth and performance of micro and small enterprises in India during the period of reforms. It provides fairly detailed analyses of policy changes for the micro and small enterprises secotr as well as empirical analyses of performance and efficiency of the unorganised manufacturing sector. it examines a range of emerging and persistent complex issues facing this crucial sector including credit, exports, trade regulations, capacity building, subcontracting, clustering, entrepreneurship and rural industrialisation. Focusing on the constraints facing this sector even during
Keywords: Micro economics